Smart Greenhouse System Based on Internet of Things using Information Flow Diagram and MQTT Connectivity - Promput, Sommart; Uraipan, Naris; Klongdee, Suttipong (Journal of Applied Informatics and Technology, 2024)
Technological advancements have driven the rapidly changing digital era, making the Internet of Things (IoT) adaptable in several study fields. Efficiently designing and developing smart greenhouse systems may enhance precision agriculture by enabling automated and accurate operations. This study concentrates on the architectural design of a smart greenhouse monitoring system. It employs Message Queue Telemetry Transport (MQTT) as a protocol to facilitate data communication between devices within the IoT system over extensive distances. This protocol works in conjunction with applications that use the Information Flow Diagram (IFD) architecture for the user interface. Additionally, the protocol evaluates the efficiency of using the smart greenhouse system with a mobile application. By assessing farmers’ acceptance of the proposed IoT system, 35 farmers explored the adoption of IoT technology for farming based on the Technology Acceptance Model (TAM) model. The evaluation of the results of the hypothesis test was analyzed using the critical ratio (CR) value, with a required limit of 1.96 at the 95% confidence level. We can conclude that all the hypotheses were acceptable.